Pembinaan Kualiti Bersepadu Menuju Keberkesanan Institusi Pengajian Tinggi Islam: Refleksi Terhadap Universiti Muhammadiyah di Indonesia - Ahmad Sahli., Tobroni (Jurnal Usuluddin, 2009)
Build a university in fact is to build civilization. Excellence university can only be built by highly civilised people. Normatively, Islam is a religion that truly appreciates the knowledge, scholars, researchers and knowledge institutions. Islamic history has also recorded the glory of Islamic civilization in the matter. Now, Muslims becomes the most lagging people in knowledge civilization. The indicators are the least Muslim scientists, lack of caliber scientific institutions, patent rights and scientific publications compared with the peoples of other religions. Universities as institutions of knowledge get less attention from Islamic governments and Islamic NGOs. Muhammadiyah is one of the few Islamic organizations that consistently worked to develop the university. Although universities are built by Muhammadiyah still on the standard of being developed, but the efforts of Muhammadiyah should be appreciated and perhaps provide inspiration for other Muslim organizations to follow its steps. This article discusses on how the empowerment of Muhammadiyah universities to become the real university or excellence university. It will elucidate on the eligibility construction, supervision of first year students, new student recruitment and scholarships, job security and quality assurance, lecturer and human resources, portofolio learning, academic culture, libraries, and information technology suppor